2009
DOI: 10.1088/0004-637x/702/1/480
|View full text |Cite
|
Sign up to set email alerts
|

Formation Criteria and the Mass of Secondary Population Iii Stars

Abstract: We explore the formation of secondary Population III (Pop III) stars under radiation hydrodynamic (RHD) feedback by a preformed massive star. To properly treat RHD feedback, we perform threedimensional RHD simulations incorporating the radiative transfer of ionizing photons as well as H 2 dissociating photons from a preformed star. A collapsing gas cloud is settled at a given distance from a 120M ⊙ Pop III star, and the evolution of the cloud is pursued including RHD feedback. We derive the threshold density d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 77 publications
(107 reference statements)
0
27
0
Order By: Relevance
“…The sign of the feedback depends on various parameters, such as the state of the collapse and the distance to the source. If a halo is close to an ionizing source or has not yet collapsed to high densities, the halo may be photoevaporated, while in other cases the halo may survive and continue to collapse Kitayama et al , 2001Susa et al 2009;O'Shea et al 2005;Mesinger et al 2006Mesinger et al , 2009Whalen et al 2008aWhalen et al , 2010Hasegawa et al 2009). Whalen & Norman (2008) and Vasiliev et al (2012b) also showed that shadow and thin-shell instabilities may develop in the ionization fronts.…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…The sign of the feedback depends on various parameters, such as the state of the collapse and the distance to the source. If a halo is close to an ionizing source or has not yet collapsed to high densities, the halo may be photoevaporated, while in other cases the halo may survive and continue to collapse Kitayama et al , 2001Susa et al 2009;O'Shea et al 2005;Mesinger et al 2006Mesinger et al , 2009Whalen et al 2008aWhalen et al , 2010Hasegawa et al 2009). Whalen & Norman (2008) and Vasiliev et al (2012b) also showed that shadow and thin-shell instabilities may develop in the ionization fronts.…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…But these models do not include the photoevaporation of the halo by the star prior to its explosion. Studies have shown that ionizing UV radiation from nearby Pop III stars can ablate the outer layers of the halo in supersonic flows and expose its interior to the IGM (Shapiro et al 2004;Iliev et al 2005;O'Shea et al 2005;Susa & Umemura 2006;Susa 2007;Hasegawa et al 2009;Susa et al 2009;Whalen et al 2010). The dense core casts a cylindrical shadow that is eventually crushed down into the axis of the halo by thermal pressure forces in the surrounding ionized gas.…”
Section: Introductionmentioning
confidence: 99%
“…We note that for star formation to be suppressed by the photoionizing background during reionization, the minihalo must be subjected to the radiation before it reaches advanced stages of collapse, as an ionization front passing through a dense minihalo may act to induce star formation, not to prevent it (e.g. Ahn & Shapiro 2007; Whalen et al 2008a; Susa, Umemura & Hasegawa 2009). Therefore, we make the simple, conservative assumption that the gas collapsing into minihaloes with masses higher than M minihalo = 10 6 M ⊙ [(1 + z )/10] −3/2 , corresponding to virial temperature T vir ∼ 2 × 10 3 K (see e.g.…”
Section: Conditions For Population III Star Formation After Reionizmentioning
confidence: 99%